Genetic Polymorphism in Peripartum Cardiomyopathy - Ivana Purnama Dewi; Johanes Nugroho (Gynecology Obstetrics & Reproductive Medicine)
Peripartum cardiomyopathy (PPCM) is a rare type of cardiomyopathy. PPCM is a potentially life-threatening pregnancy-associated disease that typically arises in peripartum period and is marked with left ventricular (LV) dysfunction and heart failure. The cause of PPCM remain unclear, but several mechanisms have been proposed ehich indices a potentially multi-factorial etiology. Early case reports identified overlap between familial dilated cardiomyopathy (DCM) and PPCM, although the degree of overlap is largely unknown. Many evidence supporting a contribution from gene mutations in PPCM includes genome-wide association studies, familial occurrence, variable prevalence among different regions and ethnicities, and more recent investigations of panels of genes for mutations among women with PPCM. Although the true incidence of genetic cardiomyopathy is not yet known among women with PPCM, there is substantial evidence demonstrating that genetic contribution to their condition.